Evaluasi Pelaksanaan Kegiatan Ekstrakurikuler Seni Tari di SD Islam Terpadu Al-Akhyar - Wiwit Syafa’atul Fadhilah; Raida Fitri Sabrina; Inesya Kalyana Tantri; Fina Fakhriyah; Erik Aditia Ismaya (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
This study aims to evaluate the implementation of extracurricular dance activities at Al-Akhyar Integrated Islamic Elementary School using the CIPP model. The results of this study determine that extracurricular dance activities at Al-Akhyar Integrated Islamic Elementary School have met the standards set in the national guidelines regarding the involvement and management of implementing personnel. The program has had a positive impact on students and the school, such as enhancing students' creativity, discipline, and self-confidence, as well as improving the school's image and reputation. However, this study also identified some weaknesses, such as a decrease in the number of participants after September and a lack of human resources involved in the extracurricular activities. Therefore, this study recommends several improvements, such as enhancing the promotion of extracurricular programs, improving the quality of instructors, and increasing parental involvement in extracurricular activities.